2018
DOI: 10.1063/1.5030699
|View full text |Cite
|
Sign up to set email alerts
|

Deep and fast free-space electro-absorption modulation in a mobility-independent graphene-loaded Bragg resonator

Abstract: Deep and fast electro-optic modulation is critical for high-speed near infrared signal processing. We combine the electro-absorption tunability of graphene with the high-Q resonance of a Bragg-based Fabry-Perot resonator at λ=1550 nm and show that ~100% free-space signal modulation (>50 dB extinction ratio, <1 dB insertion loss) at high speed (>1 GHz) can always be achieved independently of graphene quality (mobility), provided the device is operating in reflection mode and tuned in critical coupling with grap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In addition to modulation depth, the operation speed is also used to describe the structure performance of the graphene modulator, which can be estimated by the formula [28] f = 1 2πRC…”
Section: Resultsmentioning
confidence: 99%
“…In addition to modulation depth, the operation speed is also used to describe the structure performance of the graphene modulator, which can be estimated by the formula [28] f = 1 2πRC…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, borophene is a 2D metal that supports intrinsic plasmonic response with stronger field confinement than the traditional noble bulk metals in the considered nearinfrared region, significantly improving the electroabsorption of graphene. On the other hand, borophene plasmons allows us to realize the active modulation of graphene electroabsorption in a wide waveband, which is not possible for previous reported strategies that based on bulk metallic plasmons, [18] F-P cavity resonance, [26][27][28][29] guide-mode resonance [31][32][33][34][35][36][37] or magnetic polaritons. [38][39][40][41][42][43]…”
Section: Active Modulation Of Graphene Electroabsorption In a Wide Wa...mentioning
confidence: 99%
“…Such phenomenon can be attributed to the different absorption property of doped graphene at different wavelength region. [18,32,34,35,41,54] It should be mentioned that, from the ultraviolet to nearinfrared wavelength region, graphene itself is unable to excite surface plasmon resonances and its absorption is due to direct interband transitions determined by its Fermi energy E f . By plotting the real and imaginary parts of graphene permittivity in Figure 1f, it is found that there is a sharp peak in the real part and a sudden fall in the imaginary part at 1.72 µm (corresponding to the optical energy of 0.72 eV, i.e., 2E f ).…”
Section: Electroabsorption Modulation Mechanism and Device Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies [16,31,32] and experiments [33][34][35][36][37] in integrated nonlinear waveguide devices followed, which paved the way toward voltage-tunable ultrafast absorptive and refractive nonlinearity in photonics. While the interested audience awaits for more integrated nonlinear devices and experiments, work progresses in designing new components [38][39][40][41][42][43][44][45][46][47] and extending the theoretical modeling horizons [48][49][50][51][52][53][54][55].…”
mentioning
confidence: 99%